Investigating the content and correlates of undergraduate students' academic regrets - John Ranellucci (Frontiers in Psychology)
IntroductionThe types of academic regrets that college students experience, characteristics of these regrets, and relations to motivational and emotional outcomes were investigated in two studies.MethodsStudy 1 (N = 152) explored the relations between students' most severe academic regret and outcomes in general university courses, whereas Study 2 (N = 128) explored these relations in the context of a large introductory computer science course.ResultsAcross both studies, results suggested that students report various academic regrets. Generally, the types of regrets were unrelated to regret intensity, amounts of intrusive thoughts, or whether regrets were considered an omission or commission. Results further suggested that higher regret intensity was associated with motivational and emotional outcomes in the context of general university courses (Study 1), but not in the context of a specific undergraduate computer science course (Study 2).DiscussionResults are discussed within control-value theory and situated expectancy-value theory. Implications for practice are shared.